Regime macroeconômico e o projeto social-desenvolvimentista - Pedro Rossi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In the recent debate on the Brazilian growth model, the accuracy of the economic tripod (inflation targeting, primary fiscal target and floating exchange rate regimes) was pointed out as being responsible for the lowering of Brazilian economic growth and as a hindrance to its development. However, over time the macro regime has proved to be flexible and allowed changes in the form of management of policies, within the same institutional framework, especially after the 2008 crisis. Within this context, the present chapter aims to discuss the relationships between these macroeconomic policy fronts and a social oriented development strategy for the Brazilian economy. The background question is if the actual macroeconomic regime, inherited from an orthodox perspective, is compatible with the deepening of a social oriented development, which depends on a strong role of the State, income distribution and expansion of social infrastructure.
Keywords: O11; O23; E50; E62; 330; social developmentalism; economic tripod; State